2021
DOI: 10.1111/dth.14815
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab: A complete approach to psoriatic patients—Real‐world evidence study

Abstract: Psoriasis is a chronic and debilitating immune-mediated inflammatory disease, associated with an increased risk for comorbidities and a substantial psychologic and socioeconomic impact that can last a lifetime, 1,2 for which secukinumab has demonstrated high efficacy and a very favorable safety profile in several real-world studies. 3-6 This retrospective single-center cohort study collected data from 66 patients treated with secukinumab up to 40 weeks in a real-world setting, and evaluated secukinumab drug su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The proportions of patients who achieved PASI 75/90 in this study are consistent with those reported earlier, albeit the duration of the studies reported were diverse, ranging from 40 to 104 weeks[ 15 17 ]. Moreover, the PASI 75/90 response rates in our study were higher than those reported in the pivotal phase 3 secukinumab studies ERASURE and FIXTURE in patients receiving secukinumab 300 mg [ 5 ].…”
Section: Discussionsupporting
confidence: 90%
“…The proportions of patients who achieved PASI 75/90 in this study are consistent with those reported earlier, albeit the duration of the studies reported were diverse, ranging from 40 to 104 weeks[ 15 17 ]. Moreover, the PASI 75/90 response rates in our study were higher than those reported in the pivotal phase 3 secukinumab studies ERASURE and FIXTURE in patients receiving secukinumab 300 mg [ 5 ].…”
Section: Discussionsupporting
confidence: 90%